1997
DOI: 10.1116/1.580600
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interfacial and electronic properties of annealed Pd/SiC and Pd/SiO2/SiC Schottky diode sensors

Abstract: Schottky diodes composed of palladium deposited on silicon carbide (Pd/SiC) detect hydrogen and hydrocarbon gases at elevated temperatures with high sensitivity. Previous examination of the properties of the Pd/SiC structure indicated that its forward current responded to the presence of hydrogen even after extended annealing at 425 °C. However, drift in the sensor properties suggested that stabilization of the diode structure was necessary. In this work, we examine the effects of placing a thin layer of silic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…Several studies concerning these properties have been reported in the literature [2][3][4][5]. Of particular interest is the study of the physical properties of its junctions with metals, since the reliability of the devices highly depends on the stability of their contacts [6][7][8][9][10][11][12]. In the present work, electron microscopy and atomic force microscopy (AFM) are used to clarify which are the experimental conditions for the growth of Pd thin films on 6H-SiC.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies concerning these properties have been reported in the literature [2][3][4][5]. Of particular interest is the study of the physical properties of its junctions with metals, since the reliability of the devices highly depends on the stability of their contacts [6][7][8][9][10][11][12]. In the present work, electron microscopy and atomic force microscopy (AFM) are used to clarify which are the experimental conditions for the growth of Pd thin films on 6H-SiC.…”
Section: Introductionmentioning
confidence: 99%
“…After annealing at temperature higher than 1073 K some specimens presented Pd 3 Si and Pd 2 Si phases while other specimens presented only Pd 2 Si phase [22][23][24].…”
Section: Discussionmentioning
confidence: 97%
“…Pd content in the buffer, IPyC and outer pyrolytic carbon (OPyC) was significantly lower than that around the SiC layer indicating a trap or stabilization mechanism in this vicinity. From previous studies [1][2][3] and [8], it is known that Pd forms a silicide when heated in contact with SiC and this lowers the concentration of free Pd in the area and acts as a sink for Pd. Fig.…”
Section: Pd and Ag In Triso Particlesmentioning
confidence: 98%